Physical Slope Stability: Factors of Safety Under Static and Pseudo-Static Conditions - Cecilia Arriola; Eddie Aronés; Violeta Vega; Doris Esenarro; Geofrey Salas; Anjhinson Romero; Vanessa Raymundo (Infrastructures)
Evaluating physical slope stability is essential to prevent landslides and damage to infrastructure located on sloping terrains. This study analyzes how static and pseudo-static conditions affect slope safety, considering the magnitude and location of the loads exerted. A total of 2394 simulations were carried out on 399 terrain profiles, using the Spencer method to calculate factors of safety (FSs). The results reveal that uniformly distributed loads placed at the center of the slope increase stability under static conditions. However, in pseudo-static scenarios, the action of dynamic forces, such as seismicity, drastically reduces the FS, especially on slopes greater than 15%. This analysis allowed the identification of critical zones of high susceptibility, promoting the implementation of reinforcement techniques, such as retaining walls and drainage systems. In addition, zoning maps were developed that prioritize safe areas for urban development, aligned with the international standards. The findings underscore the importance of integrating predictive models into design and planning processes, considering both static and dynamic factors. In conclusion, this study provides practical tools for risk mitigation and resilient infrastructure design in sloping terrains.